Efficacy of music therapy as a non-pharmacological measure to support alzheimer's disease patients: a systematic review - Jia Wang; Cong Liu; Ying Dai; Can Mei; Guiping Wang; Yong Wang; Tao Huang; Jianbo Zhan; Jing Cheng (BMC Geriatrics)
Abstract Background Alzheimer's disease (AD) is a degenerative disease of the central nervous system characterized by progressive memory degradation and language and behavior disorders. Apart from curative pharmacological therapies, music therapy (MT) has been diffusely used as an efficient and economical non-pharmacological treatment for AD patients in recent years. Methods Three databases (PubMed, Web of Science and PsycINFO) were searched to analyse the efficacy of MT in patients with AD. Keywords included "Alzheimer's disease", "AD", "Mild Cognitive Impairment", "MCI", "music" and "music therapy". Results Literatures between January 2013 and January 2023 were selected, with 42 literatures included in the study, which highlights the beneficial impact of MT on cognition (memory, attention, language), behavioural and psychological symptoms (anxiety, depression and agitation), quality of life, self-esteem and physical pain in AD patients. Conclusion MT is a promising non-pharmacological treatment approach for individuals living with AD. However, further evidences from prospective, randomised, blinded, uniform, and rigorous method-logical investigations in this field are required to conclusively validate MT's impact on this disease. PROSPERO registration number CRD420251034039. Graphical Abstract